Heterogeneous Expectations, Optimal Monetary Policy, and the Merit of Policy Inertia - Emanuel Gasteiger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
The design and analysis of optimal monetary policy is usually guided by the paradigm of homogeneous rational expectations. Instead, we examine the dynamic consequences of implementation strategies, when the actual economy features expectational heterogeneity. Agents have either rational or adaptive expectations. Consequently the central bank's ability to achieve price-stability under heterogeneous expectations depends on its objective and implementation strategy. An expectations-based reaction function, which appropriately conditions on private sector expectations, performs exceptionally well. However, once the objective introduces policy inertia, popular strategies can fail. These results call for new implementation strategies under interest rate stabilization.
Keywords: E52; D84; D83; 330